Intracavity Squeezing Can Enhance Quantum-Limited Optomechanical Position Detection through Deamplification - Peano, Vittorio; Schwefel, Harald; Marquardt, Christoph; Marquardt, Florian (Physical Review Letters, 2015)
It has been predicted and experimentally demonstrated that by injecting squeezed light into an optomechanical device, it is possible to enhance the precision of a position measurement. Here, we present a fundamentally different approach where the squeezing is created directly inside the cavity by a nonlinear medium. Counterintuitively, the enhancement of the signal-to-noise ratio works by deamplifying precisely the quadrature that is sensitive to the mechanical motion without losing quantum information. This enhancement works for systems with a weak optomechanical coupling and/or strong mechanical damping. This can allow for larger mechanical bandwidth of quantum-limited detectors based on optomechanical devices. Our approach can be straightforwardly extended to quantum nondemolition qubit detection.
CRIS-Team Scopus Importer:2022-06-05